The indigenous and their independence process: Huarochirí from the end of 1820 to May 1821 - Asencio, Erik Felix (2021)
The new documentation on the independence of Peru, together with the memories of the participants themselves of this historical event, have allowed that the courageous participation of the huarochirano indigenous for the emancipation can be constructed and described in the present investigation, since the end of 1820, with the formation of the first guerrilla party under the command of Quispe Ninavilca and José Manrique, until May 1821, that is, shortly before the start of the second campaign to the Sierra de Arenales. The beginning of the formation of the Huarochiranas is described, as well as their first confrontations with the royalist forces, mainly with those commanded by Monet and Valdez in strategic points in the area such as San Mateo and Carampoma.